Cell death mechanisms in tumoral and non-tumoral human cell lines triggered by photodynamic treatments: apoptosis, necrosis and parthanatos - Soriano, Jorge; Mora-Espí, Inma; Alea-Reyes, Maria E.; Pérez-García, Lluïsa; Barrios, Leonardo; Ibáñez, Elena; Nogués, Carme (Nature Publishing Group, 2017)
Cell death triggered by photodynamic therapy can occur through different mechanisms: apoptosis, necrosis or autophagy. However, recent studies have demonstrated the existence of other mechanisms with characteristics of both necrosis and apoptosis. These new cell death pathways, collectively termed regulated necrosis, include a variety of processes triggered by different stimuli. In this study, we evaluated the cell death mechanism induced by photodynamic treatments with two photosensitizers, meso-tetrakis (4-carboxyphenyl) porphyrin sodium salt (Na-H2TCPP) and its zinc derivative Na-ZnTCPP, in two human breast epithelial cell lines, a non-tumoral (MCF-10A) and a tumoral one (SKBR-3). Viability assays showed that photodynamic treatments with both photosensitizers induced a reduction in cell viability in a concentration-dependent manner and no dark toxicity was observed. The cell death mechanisms triggered were evaluated by several assays and cell line-dependent results were found. Most SKBR-3 cells died by either necrosis or apoptosis. By contrast, in MCF-10A cells, necrotic cells and another cell population with characteristics of both necrosis and apoptosis were predominant. In this latter population, cell death was PARP-dependent and translocation of AIF to the nucleus was observed in some cells. These characteristics are related with parthanatos, being the first evidence of this type of regulated necrosis in the field of photodynamic therapy.